Severe lymphopenia acquired during chemoradiotherapy for esophageal cancer: Incidence and external validation of a prediction model. (October 2021) - Kroese, Tiuri E.; Jairam, Jasvir; Ruurda, Jelle P.; Lin, Steven H.; Mohan, Radhe; Mook, Stella; Haitjema, Saskia; Hoefer, Imo; Haj Mohammad, Nadia; Peters, Max; van Hillegersberg, Richard; van Rossum, Peter S.N.
Highlights: More grade 4 lymphopenia in extended-CROSS compared with CROSS CRT. Grade 4 lymphopenia was associated with a reduced overall survival. The pretreatment prediction model demonstrated good external performance. The model identifies patients at high-risk for grade 4 lymphopenia. The model could identify patients eligible for lymphopenia-mitigating strategies. Abstract: Background: The incidence of grade 4 lymphopenia in patients treated with chemoradiotherapy (CRT) according to Chemoradiotherapy for Oesophageal cancer followed by Surgery Study (CROSS) regimen is unclear. The primary aim was to determine the incidence of grade 4 lymphopenia during CROSS for esophageal cancer. Secondary aims were to externally validate a prediction model for grade 4 lymphopenia and compare overall survival between patients with and without grade 4 lymphopenia. Methods: Patients who underwent CRT for esophageal cancer between 2014 and 2019 were eligible for inclusion. Patients with a planned radiation dose of 41.4 Gy (CROSS) or 50.4 Gy ("extended-CROSS") and concurrent carboplatin and paclitaxel were included. The primary outcome was the incidence of grade 4 lymphopenia during CRT defined according to Common Terminology Criteria for Adverse Events version 5.0 (i.e. lymphocyte count nadir < 0.2 µL). The secondary outcome measures were the prediction model's external performance (i.e. discrimination and calibration). Overall survival for patients with versus without grade 4 lymphopenia was compared using Kaplan–Meier analysis. Results: A total of 219 patients were included of whom 176 patients (80%) underwent CROSS and 43 patients (20%) extended-CROSS. The incidence of grade 4 lymphopenia was 11% in CROSS and 33% in extended-CROSS ( p  < 0.001). External discrimination yielded a c-statistic of 0.80 (95% confidence interval: 0.70–0.89). External calibration of the model was poor in CROSS but fair in extended-CROSS. Adjusted calibration using intercept correction (adjusted for the lower a-priori risk for grade 4 lymphopenia in CROSS) showed fair agreement between the observed and predicted risk for grade 4 lymphopenia. Median overall survival in patients with versus without grade 4 lymphopenia was 12.7 versus 42.5 months ( p  = 0.045). Conclusion: The incidence of grade 4 lymphopenia is significantly higher in esophageal cancer patients receiving extended-CROSS compared to those receiving CROSS. The prediction model demonstrated good external performance in the setting of the CROSS-regimen and could be used to identify patients at high-risk for grade 4 lymphopenia who might be eligible for lymphopenia–mitigating strategies.